Arranging for horns - Gates, Jerry (Berklle Press,, 2015)
Write for a horn section! In this book, you will learn how to add saxophones and brass to a rhythm section ensemble. You will learn the capabilities and characteristics of the most common instruments, and how to order them effectively. You will also learn the different roles that a horn section can serve in your ensemble. Online audio tracks demonstrate the key concepts, as exemplified in a complete score. Online audio is accessed at halleonard.com/mylibrary